Hell before their very eyes: American soldiers liberate concentration camps in Germany, April 1945 - McManus, John C. (Witness to history, 2015)
Encountering Ohrdruf -- "The smell of death was thick in the air": witnessing Buchenwald -- Treating Buchenwald: medicine and Murrow -- Dachau: the approach -- "My heart was going a mile a minute": liberating Dachau -- Dachau: the impact